AMELIORATION OF CADMIUM STRESS ON TOMATO (LYCOPERSICON ESCULENTUM) BY TRIACONTANOL APPLICATION - SAEED, MA; SHAHEEN, MR; HUSSAIN, R; ANJUM, S; SARWAR, M; SHABBIR, A; TARIQ, MBE (Biological and Clinical Sciences Research Journal, 2023)
Lead (Pb), copper (Cu), zinc (Zn), and cadmium (Cd) tend to build up in the roots of tomato plants and are then taken up by the leaves and fruits, resulting in significant removal from the soil. Plant growth and development are at risk due to the soil's buildup and toxicity of heavy metals (HMs). Cadmium, a hazardous element, inhibits the development and yield of tomatoes. Triacontanol (TRIA) enhances plant development when exposed to low concentrations of Cd, hence mitigating its harmful effects. This work used the exogenous triacontanol (TRIA) application to mitigate the adverse physiological impacts of cadmium (Cd) on tomato plants. The current study investigated tomatoes' physical characteristics, functions, and chemical composition to get a deeper understanding of how Triacontanol responds to stress caused by cadmium. Two experiments were laid out under a Completely Randomized Design (CRD), and three replications under a hydroponic system. In the first experiment, the effects of Cd on tomato were grown hydroponically and exposed to cadmium chloride at five concentration levels (control, 1.5, 03, 06 and 12µmol/L). While in the second experiment tomato grown hydroponically, and cadmium used in the form of CdCl2 at five concentration levels (control, 1.5, 03, 06 and 12µmol/L) with one level of TRIA 10µM/L was be applied to facilitate the Cadmium stress on plant. The Hoagland's solution was used to irrigate the plants after the initial 72 hours of pretreatment in both experiments at 35±1℃; 70-75%RH. Data for tomato plants' morphological, physiological, and biochemical characteristics was recorded. Results revealed that mitigation through triacontanol (TRIA) @ 10µmol/L best affects cadmium stress. It was noted that triacontanol (TRIA) @ 10µmol/L significantly affects tomato plants' morphological, enzymatic, and physiological characteristics at 1.5µmol/L of cadmium stress.